MODEL SELF EFFICACY DAN EMPLOYEE EMPOWERMENT TERHADAP KINERJA KARYAWAN PADA TRUNTUM KUTA HOTEL - PERMATASARI, INTAN DWI; DEWI, NYOMAN INDAH KUSUMA; SITAWATI, ANAK AGUNG RAKA (Universitas Mahasaraswati K. Mataram, 2024)
This study aims to analyse the effect of self efficacy and employee empowerment partially and simultaneously on employee performance at Truntum Kuta Hotel, and to determine the model of self efficacy and employee empowerment on employee performance at Truntum Kuta Hotel. The population of this study amounted to 153 people who were permanent employees and contract employees, with a sample size of 60 people. Data collection from samples is done by distributing online questionnaires in the form of google forms. The data analysis technique used is descriptive statistical analysis, partial least squares (PLS) analysis and regression analysis (simultaneous f test) using SmartPLS v.4.1.0.0 software. The results of this study indicate that each variable of self efficacy and employee empowerment has a positive and significant effect partially on the performance of Truntum Kuta Hotel employees, self efficacy and employee empowerment have a positive and significant effect simultaneously on the performance of Truntum Kuta Hotel employees. The model of self efficacy and employee empowerment on the performance of Truntum Kuta Hotel employees is based on dimensions that have been measured.